Development of Learning for Memorizing Surah Al-Ma'un Based on Puzzle Game for Seven-Year-Old Children - Nurchari, Muadz Rasyid; Faradiella, Elvynanda; Fiddarain, Zaduna; Nabila, Laili; Fitria, Laila Annis; Asmoro, Secoundio Rabbanissa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The Quran education in early childhood is an integral part of an achievement aiming to develop potential in children. Innovative game-based approaches have been introduced to improve the effectiveness of Quran learning, one of which is through puzzle-based games. The author tries to analyze the strategies applied in integrating gaming technology into the context of learning the Koran. A qualitative study is likely sufficient to identify improvements in children's participation and learning results in memorizing the Quran. Hopefully, puzzle-based game learning technology can develop and improve children's enthusiasm and focus while memorizing the Quran.